OrthoVenn2: a web server for whole-genome comparison and annotation of orthologous clusters across multiple species - Xu, Ling; Dong, Zhaobin; Fang, Lu; Luo, Yongjiang; Wei, Zhaoyuan; Guo, Hailong; Zhang, Guoqing; Gu, Yong Q; Coleman-Derr, Devin; Xia, Qingyou; Wang, Yi (Nucleic acids research, 2019)
OrthoVenn is a powerful web platform for the comparison and analysis of whole-genome orthologous clusters. Here we present an updated version, OrthoVenn2, which provides new features that facilitate the comparative analysis of orthologous clusters among up to 12 species. Additionally, this update offers improvements to data visualization and interpretation, including an occurrence pattern table for interrogating the overlap of each orthologous group for the queried species. Within the occurrence table, the functional annotations and summaries of the disjunctions and intersections of clusters between the chosen species can be displayed through an interactive Venn diagram. To facilitate a broader range of comparisons, a larger number of species, including vertebrates, metazoa, protists, fungi, plants and bacteria, have been added in OrthoVenn2. Finally, a stand-alone version is available to perform large dataset comparisons and to visualize results locally without limitation of species number. In summary, OrthoVenn2 is an efficient and user-friendly web server freely accessible at https://orthovenn2.bioinfotoolkits.net.